The Needs to Establish an Integrated Safety System for Express Bus - H. Azman, A.; S.K. Singh, S.; G.W. Aizon, W.; Hishamuddin, H.; R.M. Yazid, M.; Abdullah, S.; K. Ariffin, A.; A. Wahab, A.; Atiq, R.; S. Solah, M.; Hamzah, A. (International Journal of Engineering and Technology, 2018)
The aim of this paper is to present an analysis of the safety of express buses in Malaysia by providing an overview on road accidents involving express buses, current road safety enforcement and regulations, and driving comfort and safety in Malaysia. Bus accident is a major public concern in Malaysia as they often involve the lives of innocent victims. Redundancy of regu lations and enforcements by different agencies and the lack of safety management capabilities of the bus industry have been identified as the main issues in express bus transportation. Bus drivers are more likely to exceed the speed limit due to the lack of enforcement and low traffic volume during the night compared to during the day. Hence the discussion will highlight the current enforcement, safety policy, regulatory proc ess and riding comfort of the driver as the major factors that deals with safety of both the vehicle and passengers. Â Therefore, it is crucial to tackle the highlighted parameters in terms of managing road accidents of express buses. Various operational management must also be ad- dressed to improve enforcement and safety management of roadside hazards.Â Â